A tailored highly solvating electrolyte toward ultra lean-electrolyte Li–S batteries - Zixiong Shi; Simil Thomas; Zhengnan Tian; Dong Guo; Zhiming Zhao; Yizhou Wang; Shuo Li; Nimer Wehbe; Abdul-Hamid Emwas; Osman M. Bakr; Omar F. Mohammed; Husam N. Alshareef (Nano Research Energy)
Low electrolyte usage is a key to attaining high-energy-density lithium–sulfur (Li–S) batteries. However, this is still a tremendous challenge for traditional ether-based electrolytes that follow a dissolution–precipitation mechanism. Highly solvating electrolytes, which can facilitate polysulfide dissolution and alter reaction pathway, are considered a promising strategy. Nonetheless, mechanistic understanding and kinetic evaluation remain insufficient while the principle of Li2S nucleation and dissociation has not been elucidated. Herein, we unveil the Li-ion solvation and polysulfide speciation in the solvents with different denticity and donicity. The origin of S3•– radical-directed path and three-dimensional Li2S precipitation in high-donicity electrolytes has been uncovered. It is revealed that ammonium ions enable the facile dissolution and dissociation of Li2S via Lewis acid-base interaction and H···S2– binding. Consequently, Li–S batteries with a low electrolyte and sulfur (E/S) ratio of 5 μL·mgs–1 achieve a high capacity of 1092 mAh·g–1. Even at a harsh E/S ratio of 3 μL·mgs–1 and a high sulfur loading of 4 mg·cm–2, they still sustain a stable operation over 30 cycles. Our work sheds light on the underlying reaction mechanism and rationalizes the design of highly solvating electrolytes, which in turn opens a new avenue for achieving pragmatic lean-electrolyte Li–S batteries.